1991
DOI: 10.2307/3563341
|View full text |Cite
|
Sign up to set email alerts
|

Medical Ethics in Ireland: A Decade of Change

Abstract: As the ethical framework of the Catholic Church becomes incapable of accommodating the cultural diversity in Ireland, the search for a new moral discourse takes on a greater urgency. In its absence, litigation in Ireland is on the increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Finally, we have limited data on what motivates NHVs to participate in phase 1 trials. In the United States and elsewhere, money appears to be a significant motivating factor for some research participation, and the less well-off may be more motivated than others to participate in phase 1 trials (Hassar et al, 1977; Novak, Seckman, & Steward, 1977; Robertson, 1986; Bigorra and Banos, 1990; Dooley, 1991; McNeil, 1993, 176; Tishler and Bartholomae, 2002; Tishler and Bartholomae, 2003). For example, Kirkpatrick found that “money is the primary reason young [mean age 28] and elderly [mean age 72] volunteers participate in their first drug study and the primary reason young volunteers participate in subsequent studies” (1991, 109).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we have limited data on what motivates NHVs to participate in phase 1 trials. In the United States and elsewhere, money appears to be a significant motivating factor for some research participation, and the less well-off may be more motivated than others to participate in phase 1 trials (Hassar et al, 1977; Novak, Seckman, & Steward, 1977; Robertson, 1986; Bigorra and Banos, 1990; Dooley, 1991; McNeil, 1993, 176; Tishler and Bartholomae, 2002; Tishler and Bartholomae, 2003). For example, Kirkpatrick found that “money is the primary reason young [mean age 28] and elderly [mean age 72] volunteers participate in their first drug study and the primary reason young volunteers participate in subsequent studies” (1991, 109).…”
Section: Introductionmentioning
confidence: 99%